(untitled) (Tribhuvan University Law Journal, 2025)
The traditional development of investment treaties are largely based on model developed across region and most of them are able to reflect the notion of investorstate dispute settlement mechanism (ISDS). The ISDS is considered as integral part of any investment treaties and hence mostly are seen in south Asian bilateral investment treaties also. The issues of conflict with investor- and host state may be for multiple reasons and environment is becoming one. The way environment was sidelined for years and years as subject matters of protection in the investment treaties, today it is compelling both the investor and host stake to take care during and aftermath the protection of environment issues. The way classical bilateral investment treaties were used to draft has inherent low interest to protect the environmental concerns. The less attention to these aspects in the treaties were also not well reflected in the dispute settlement mechanism. The preamble also saying the concerns on the protection of environment as subject matter of investment treaties. This expression of environment in the investment treaties are not similar and hence has multiple way of protection regime. The perambulatory expression in BIT and TIP also shows host state interest towards protection of environment considering and making proper balance with the right of investor’s and their interest. The TIP is not merely designed to talk about the investment issues rather the investment is considered as one component among others. This paper has analyzed the BIT of South Asian regions limiting to South Asian Association for Regional Cooperation (SAARC) region in protection of environment and the issues relating to dispute settlement.